Company Characteristics, Profitability, and Financial Performance Through Corporate Social Responsibility: Karakteristik Perusahaan, Profitabilitas, dan Kinerja Keuangan Melalui Tanggung Jawab Sosial Perusahaan - Hanis, Priyanka Anisa; Fitriyah , Hadiah (Indonesian Journal of Law and Economics Review, 2024)
Background: Financial performance is vital for assessing a company's sustainability, influenced by various internal factors. Specific Background: Although Corporate Social Responsibility (CSR) is recognized as significant, its mediating role between company characteristics and profitability on financial performance remains underexplored. Knowledge Gap: Existing studies inadequately address CSR's interaction with these variables in manufacturing contexts. Aims: This research investigates CSR's mediating capacity in the relationship between company characteristics (size, leverage, board composition) and profitability on financial performance. Results: Employing quantitative methods and purposive sampling, findings show that company size, board of commissioners, and profitability do not significantly affect financial performance, while leverage and CSR do. Additionally, profitability positively influences CSR, but other characteristics do not. CSR mediates the relationship between profitability and financial performance but not the others. Novelty: This study enhances understanding of CSR's mediating role, focusing on specific company characteristics and profitability. Implications: The results highlight the importance of CSR initiatives for improving financial performance, offering valuable insights for corporate managers and policymakers. Highlights : CSR mediates profitability's relationship with financial performance. Company size and board composition do not impact financial performance. Leverage significantly affects financial performance and CSR. Keywords: Corporate Social Responsibility, Financial Performance, Profitability, Company Characteristics, Leverage